Negative halo effects of sustainable packaging - Techawachirakul, Monin (2024)
More firms are adopting “green packaging” due to regulatory and environmental concerns. The alcoholic beverage industry has recently joined the lobby and major producers have introduced creative paper bottles for their alcoholic drinks. Previous research on sustainable labeling (e.g., eco-friendly labels) has shown the positive halo effect where sustainable labeling induces positive evaluations. In contrast, our research aims to reveal the negative halo effects of sustainable packaging in the case of paper-bottled alcoholic beverages. Across three studies, we explore consumers' perceptions toward alcoholic drinks packed in innovative paper bottles. Studies 1–2 demonstrate that consumers hold inferior expectations (i.e., sensory attributes, price, and purchase likelihood) toward alcoholic beverages packed in paper bottles. Study 3 demonstrates that the enforced messaging and attractive packaging can mitigate the negative halo effect for self-consumption and gifting. These findings contribute to the literature on sustainable packaging, especially in the novel space of paper-bottled alcoholic drinks.